Optimizing pharmacokinetics/pharmacodynamics of β-lactam/β-lactamase inhibitor combinations against high inocula of ESBL-producing bacteria. (10th October 2020) - Tam, Vincent H; Abodakpi, Henrietta; Wang, Weiqun; Ledesma, Kimberly R; Merlau, Paul R; Chan, Katrina; Altman, Rachel; Tran, Truc T; Nikolaou, Michael; Sofjan, Amelia K
Abstract: Objectives: Reduced in vitro β-lactam activity against a dense bacterial population is well recognized. It is commonly attributed to the presence of β-lactamase(s) and it is unknown whether the inoculum effect could be diminished by a β-lactamase inhibitor. We evaluated different β-lactam/β-lactamase inhibitor combinations in suppressing a high inoculum of ESBL-producing bacteria. Methods: Three clinical isolates expressing representative ESBLs (CTX-M-15 and SHV-12) were examined. The impact of escalating β-lactamase inhibitor (tazobactam or avibactam) concentrations on β-lactam (piperacillin or ceftazidime) MIC reduction was characterized by an inhibitory sigmoid Emax model. The effect of various dosing regimens of β-lactam/β-lactamase inhibitor combinations was predicted using % T >MICi and selected exposures were experimentally validated in a hollow-fibre infection model over 120 h. The threshold exposure to suppress bacterial regrowth was identified using recursive partitioning. Results: A concentration-dependent reduction in β-lactam MIC was observed (r 2 ≥0.93). Regrowth could be suppressed in all six experiments using % T >MICi ≥73.6%, but only one out of six experiments below the threshold ( P = 0.015). The exposures to suppress regrowth might be attained using the clinical dose of avibactam, but a much higher dose than the standard dose would be needed for tazobactam. Conclusions: A dense population of ESBL-producing bacteria could be suppressed by an optimized dosing regimen of selected β-lactam/β-lactamase inhibitor combinations. The reversibility of enzyme inhibition could play an important role in diminishing the inoculum effect. In vivo investigations to validate these findings are warranted.